Subgrouping the autism "spectrum": reflections on DSM-5. - Meng-Chuan Lai; Michael V Lombardo; Bhismadev Chakrabarti; Simon Baron-Cohen (PLoS Biology)
DSM-5 has moved autism from the level of subgroups ("apples and oranges") to the prototypical level ("fruit"). But making progress in research, and ultimately improving clinical practice, will require identifying subgroups within the autism spectrum.